Complete ablation rate of percutaneous radiofrequency ablation of hepatocellular carcinoma in favorable and unfavorable locations: using real time ultrasound guidance and expandable electrode needle - Nakarin Inmutto (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).